Gender in the participatory market chain approach - Devaux, Andre; Mayanja, Sarah; Babini, Claudia; Velasco, Claudio; Flores, Paola (International Potato Center, 2017)
This presentation was given on 5 October 2017, as part of the webinar 'Gender mainstreaming in the Participatory Market Chain Approach (PMCA)'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the International Potato Center (CIP).